English Native Speakers and Indonesian Speakers’ Concept of Verb 'Increase': A Corpus-Based Lexical Semantic Approach - Sidupa, Christiana; Rahyono, F.X. (Soegijapranata Catholic University, 2025)
In conveying meaning, most Indonesian speakers still struggle in determining collocations properly, particularly for words that have the same denotative meaning in English. This research aims to reveal the English native speakers’ and the Indonesian speakers’ concept of verb ‘increase’. The semantic field in this study is based on syntagmatic relations or what is called collocation. The research method in this research adopts a combination of qualitative and quantitative approaches with descriptive and comparative methods and corpus linguistic methodological approach. The research data comes from digital texts in the field of economics of British students (British Academic Written English/ BAWE) and independent digital texts containing articles from Sinta 2 accredited national journals (Indonesian Economic Written English/ IEWE). The results show that the concept of the verb increase used by English native speakers is identical with Indonesian speakers that represents the spatial concept 'up'. Comprehending the concept, therefore, will enable Indonesian speakers to improve their comprehension of English VN collocations, as well as the accuracy of the VN collocations.